Assessing the quality of Jatropha curcas l. seeds as planting material in Sarawak - Sivasangari, A/P Jagatheeswaran (Universiti Malaysia Sarawak, (UNIMAS), 2012)
A study was conducted to evaluate the quality ofJatropha clircas seeds collected from two different accessions in Sarawak. A significant seed source variation was observed in seed morphology (colour, size and weight), seed viability, germination, moisture content, seeds storability, priming treatments, accelerated ageing, seed oil percentage and early growth performance of seed lin;) The seeds from Bintulu, Samarahan and control were dehydrated in silica gel for 0, 24, 48, 72, 96 and 120 hours then stored in six different environments for the basic seed storage; ambient room (28-30 0q, air-conditioned room (22-24 0q, refrigerator (3-5 0q, incubator (35- 40 0q, freezer (0-4 0q and liquid nitrogen (-196 0q for 4 months. Three types 0 f priming treatment used were the hydro priming, 0 smopriming and thermopriming. The average fresh weights of 10 seeds were 8.02 g, 5.94 g 7.55 g respectively, for Bintulu, Samarahan and Control seeds. Oil content was 36.75% in Bintulu, 30.37% in Samarahan and 35.49% in Control. Preliminary evaluation conducted indicated that moisture content was 18.92% for Bintulu, for 13.91% Samarahan and 17.07% for Control. Germination was 74.88, 50.10, and 70.5% for Bintulu, Samarahan and Control respectively. Viability for Bintulu, Samarahan and Control seeds were 80, 60 and 82% respectively. The dehydrated seeds at 48 hours were found successful after storing at all types of environment. The highest germination and viability percentage was obtained with seeds stored in liquid nitrogen. Seeds of J. clircas in liquid nitrogen can be stored for 163, 159, 177 days for Bintulu, Samarahan and control seeds respectively. The germination and viability percentages of J. curcas seeds from Bintulu were highest when the seeds were thermoprimed in water at 40°C as compared to other priming treatments. At 24 hour ageing the germination percentage was the highest for both accessions. Photosynthesis rates (A), stomatal conductance (gs), transpiration (E), and Chlorophyll content in Bintulu plant higher than its water stress counterpart. The seeds from Bintulu responded better germination, viability, moisture content and also with greater seed weight and size as compared to the seeds from other accessions. Overall, the seeds from Bintulu are better in its seed quality, morphologically and physiologically as compared to other accessions. The positive effect has been very favorable in terms of its quality due to the plant's potential to produce biofuel.